Examining Time to Treatment and the Role of School‐Based Health Centers in a School‐Based Sexually Transmitted Infection Program. (10th July 2018) - Sabharwal, Mallika; Masinter, Lisa; Weaver, Kingsley N.
ABSTRACT: BACKGROUND: Barriers to health care service utilization contribute to the spread of sexually transmitted infections (STIs) among teens. School‐based STI screening programs reach adolescents outside of the clinic‐based health care model and schools with school‐based health centers (SBHCs) may expedite treatment because of their proximity to the population. This study examined whether students who tested positive for STIs in a school‐based screening program had differing times to treatment based on treatment location. METHODS: All positive cases of chlamydia and gonorrhea from the 2012‐2013 school year in a Chicago Department of Public Health (CDPH) and Chicago Public Schools school‐based STI screening program were reviewed. Median time to treatment was compared for those treated at an SBHC versus those treated elsewhere (CDPH STI clinic, community health center, private physician). RESULTS: Overall, 540 students had positive results. The median age was 17 years, 427 had chlamydia (79.1%), 59 had gonorrhea (10.9%), and 54 had dual infections (10.0%); 144 were tested in a school with a SBHC on site (26.7%). Of the 483 students who received treatment (89.4%), those treated at a SBHC had a faster time to treatment compared to CDPH STI clinics (median 17 days versus 28 days, respectively, p < .001). CONCLUSIONS: For students testing positive in the Chicago school‐based STI program, time to treatment is accelerated in locations with SBHCs.